The role of sampling in an explanatory sequential mixed methods study: General applications of the transformative paradigm - Tashane K. Haynes-Brown (Methods in Psychology)
The purpose of this article is to illustrate how considerations from the transformative paradigm were integrated broadly in the sampling decisions in an explanatory sequential mixed methods study. The study sought to explore the complex relationship between teachers’ beliefs and classroom practices. Data were collected from 248 teachers using a questionnaire, semi-structured interviews, lesson observations, an observation checklist, video recordings and video elicitation interviews. By employing transformative considerations generally in making the sampling decisions a more rigorous and transparent sampling design emerged that yielded more comprehensive inferences. This article contributes to mixed methods research by providing a practical example and analytical insights into how the principles of the transformative paradigm can be applied broadly in the sampling design.